Further Investigation of the 2‐Azido‐phenylselenylation of Glycals (Eur. J. Org. Chem. 44/2021). Issue 44 (17th November 2021) - Fomitskaya, Polina A.; Argunov, Dmitry A.; Tsvetkov, Yury E.; Lalov, Andrey V.; Ustyuzhanina, Nadezhda E.; Nifantiev, Nikolay E.
Abstract : The Front Cover shows the crucial effect of stirring on the outcome of reactions of glycals with diphenyldiselenide, bis(acetoxy)iodobenzene, and sodium azide. Coffee beans depict glycals used as the starting material in both reactions. The left cup of cappuccino represents phenyl 2‐azido‐2‐deoxy‐1‐selenoglycosides, the products of azidophenylselnylation occurring upon vigorous stirring. The right cup of americano shows 1‐O‐acetyl‐2‐seleno‐2‐deoxysugars, the products of acetoxyphenylselenylation that takes place without stirring, thus leaving NaN3 out of the reaction. This study was supported by Russian Science Foundation Grant 19‐43‐02023. The authors thank Ms. Natalia Bakurova for designing the cover. More information can be found in the Full Paper by N. E. Nifantiev et al .